2011
DOI: 10.1113/jphysiol.2010.202432
|View full text |Cite
|
Sign up to set email alerts
|

Eukaryotic initiation factor 2B epsilon induces cap‐dependent translation and skeletal muscle hypertrophy

Abstract: Non-technical summary Skeletal muscle comprises ∼40% of total body mass, and the control of muscle mass has significant effects on overall health. Skeletal muscle mass is determined by the balance of protein synthesis and degradation within muscle cells. We sought to determine which cellular proteins that control protein synthesis within muscle cells are associated with muscle growth after resistance exercise, a potent growth stimulus. We identified two proteins that were associated with muscle growth in human… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
53
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 57 publications
(53 citation statements)
references
References 57 publications
0
53
0
Order By: Relevance
“…sActRIIB-Fc also increased the phosphorylation of 4E-BP1, a protein less responsive to rapamycin (12), and eIF2Bε protein. eIF2Bε is required for translation initiation, and its overexpression has induced ϳ20% hypertrophy of myofibers in mice (38). In contrast, the phosphorylation of Akt at Ser 473 increased after only 2 wk, when muscle mass was already increased, and at Thr 308 it remained unchanged.…”
Section: Discussionmentioning
confidence: 99%
“…sActRIIB-Fc also increased the phosphorylation of 4E-BP1, a protein less responsive to rapamycin (12), and eIF2Bε protein. eIF2Bε is required for translation initiation, and its overexpression has induced ϳ20% hypertrophy of myofibers in mice (38). In contrast, the phosphorylation of Akt at Ser 473 increased after only 2 wk, when muscle mass was already increased, and at Thr 308 it remained unchanged.…”
Section: Discussionmentioning
confidence: 99%
“…This included an up‐regulation of eIF2B (subunit δ) and down‐regulation of BAX, which we later confirmed by immunoblotting. The eIF2B pathway is a known translational regulator of protein synthesis, with evidence showing that its content can directly influence fibre size 31. The direct targeting of elF2B by MuRF1 appears plausible because our previous yeast two‐hybrid screens identified elF2B as a MuRF1 interacting factor, linking MuRF1 as a negative regulator of protein synthesis 32.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies with healthy human subjects, e.g., several genetic variations (Riechman et al 2004;Devaney et al 2009;Walsh et al 2012;Van Deveire et al 2012), differences in skeletal muscle gene Raue et al 2012;Phillips et al 2013) and microRNA expression (Davidsen et al 2011), phosphorylation status of signaling proteins (Mayhew et al 2011;Mitchell et al 2013), androgen receptor concentrations (Ahtiainen et al 2011;Mitchell et al 2013), and satellite cell count (Petrella et al 2008) have been suggested to segregate high and low responders to RTinduced muscle hypertrophy. The physiological aspects of individual variation in phenotype responses to RT are apparently very complex phenomena and more studies specifically focused on high and low responders are required to reveal unambiguously the mechanisms of individual differences in RT-induced adaptations.…”
Section: Discussionmentioning
confidence: 99%